FAKTOR-FAKTOR YANG MEMPENGARUHI LEMBAGA PEMBERDAYAAN MASYARAKAT KECAMATAN TAMALANREA DALAM PERENCANAAN PEMBANGUNAN DAERAH DI KOTA MAKASSAR - Hasran Hasran; Zaenal Akhmad; Rahman (Jurnal Ilmiah Administrasita', 2022)
This study aims to determine the influencing factors in optimizing the performance of Community Empowerment Institutions in Tamalanrea District, Makassar City. The type of research used is descriptive quantitative research. The basis of this research is a survey method. The population is all the components that are the object of research, therefore the objects of research are the LPM Management in Tamalanrea District, the sub-district government and the community in Tamalanrea District. The author uses a purposive sampling technique. To obtain information in accordance with the problems under study will be used: Primary data and secondary data. The data collection techniques that will be used in this study are questionnaires, observations, literature studies and documentation. The data collected through observation, documentation and literature study in this study were used as secondary data, while the data obtained from the questionnaires were analyzed quantitatively using the SPSS program. Based on the research results, it was found that the factors that influence the performance of Community Empowerment Institution management are the professionalism of Community Empowerment Institution management, accuracy of data and information, facilities and infrastructure, coordination and motivation